Relative energy deficiency in sport in rock climbers: a narrative review - Tan, K.; Schöffl, V. (The Journal of Strength and Conditioning Research, 2025)
Rock climbing has experienced immense growth in popularity over the years and was incorporated into the summer Olympic program as of the 2020 Tokyo Olympics. Previously known as Female Athlete Triad, relative energy deficiency in sport (REDs) refers to a preventable syndrome characterized by impaired physiologic functions because of low energy availability (LEA). This leads to a multitude of symptoms and compromises the health and performance of climbers. Understanding how REDs manifests in the context of climbing is important for injury prevention, ensuring safe and sustainable practices of the sport, and future research. This review comprehensively explores REDs in the setting of climbing, providing a detailed literature review including the most current research published in 2024. We shed light on the latest recommendations made by the International Olympic Committee, discuss the physiology of climbing, and review studies on anthropometry and nutrition, touching on the youth, adult, able-bodied, and para-athlete populations. Because many rock climbers take the profile of having a low BMI and body fat percentage, there is a concerning number of high-level climbers who do not meet the required nutritional status or energy requirements to sustain a moderate level of training. This article highlights the importance of implementing a multidisciplinary team-based approach in developing an individualized dietary plan for climbers with problematic LEA, underscoring the need for recognizing, diagnosing, and implementing holistic care strategies while also highlighting areas that require further advancement in the field.